Management opportunities for soil carbon sequestration following agricultural land abandonment. Issue 108 (June 2020) - Bell, Stephen M.; Barriocanal, Carles; Terrer, César; Rosell-Melé, Antoni
Highlights: Six management strategies are proposed globally following farmland abandonment. A combination of strategies achieves multiple rural development goals. Combining passive and active management can maximize soil carbon sequestration. Abandoned agricultural lands are potential resources for climate change mitigation. Abstract: The widespread historical and ongoing abandonment of agricultural lands worldwide presents important opportunities for promoting climate change mitigation through carbon sequestration. The default management outcome of abandonment is natural regeneration through ecological succession. However, several different management strategies and new land uses for abandoned agricultural lands have been recommended by the scientific community in recent years. This paper reviews the foremost proposed strategies and compares their soil carbon sequestration potentials. Six major categories have been proposed globally. Each proposal has positive and negative outcomes depending on site-specific factors and management objectives. Accordingly, no single strategy is ideal in all scenarios and a combination of strategies addresses multiple rural development goals concurrently. A combination of passive and active management techniques is the most effective approach for maximizing soil carbon sequestration over large geographic scales, while other strategies can be designed to also promote low-carbon land use practices and fossil fuel substitution. The implications of each proposal highlighted here demonstrates the positive role that abandoned agricultural lands can serve in climate change mitigation efforts, supporting policymakers tasked with planning the future of regions undergoing abandonment.